Tacrine-based Multifunctional Agents in Alzheimer's Disease: An Old Story in Continuous Development§ - Milelli, Andrea; De Simone, Angela; Ticchi, Nicole; H. Chen, Huan; Betari, Nibal; Andrisano, Vincenza; Tumiatti, Vincenzo (Current Medicinal Chemistry, 2017)
Background: The design of multifunctional agents represents one of the most active research field in medicinal chemistry. In particular, tacrine, a well known Acetylcholinesterase inhibitor, is one of the most used starting point to develop multifunctional ligands and hundreds of papers report about these new agents. This is the third review of a series concerning tacrinebased multifunctional ligands; in particular, in the present, we will summarize and discuss the most intriguing examples of tacrine-based multifunctional agents published since 2013 until 2016. Methods: We analyzed the bibliographic databases for peer-reviewed publications concerning tacrine-based multifunctional agents possessing biological actions that go beyond the simple “cholinergic” blockage. These papers have been subdivided according to their biological activities. Since this is the third review of a series, we took into considerations only the papers appeared since 2013 until 2016. Results: In this review, we have analyzed more than 33 papers. All the reported compounds retain good inhibitory activity towards acetyl- and butyryl-cholinesterase. The other biological activities concern mostly inhibition of a) β-amyloid aggregation, b) β-secretase, c) monoamino oxidases, modulation of Τ and ROS and metal chelation. Conclusion: The analysis of the current literature reported in this review confirm the importance of tacrine as scaffold to develop multifunctional agents potentially usefull to contrast Alzheimer's disease. Furthermore, the compounds herein reported showed very intriguing biological activities that could be used as starting point to develop new compounds even more interesting and, hopefully, clinically usefull to contrast Alzheimer's Disease.
Keywords: acetylcholinesterase inhibitors